The lung development, aging and the environment - Harding, Richard 1944-; Pinkerton, Kent Ed 1950- (Elsevier/AP, 2015)
The second edition of The Lung: Development, Aging and the Environment provides an understanding of the multi-faceted nature of lung development, aging, and how the environment influences these processes. As an essential resource to respiratory, pulmonary, and thoracic scientists and physicians it provides an interface between the "normal" and "disease" cluster of chapters, allowing for a natural complement to each other. The interface between different lung diseases affecting the pediatric lung also adds a useful source for comparing how different lung diseases share key pathophysiological features